Juridical Analysis of the Amendment of Law of the Corruption Eradication Commission in Eradicating Corruption from Legal and Economic Perspective - Hulman Siregar (Journal of Morality and Legal Culture, 2020)
In this case, the efforts to eradicate corruption by law enforcement officials, prosecutors of the Republic of Indonesia, and Indonesian police, have not been significant. To make the eradication of corruption useful corresponding to the mandate of law, then the Corruption Eradication Commission (KPK) was formed; this institution is known as the super body institution. The method used in this research is combining normative juridical methods with empirical facts to analyze the effectiveness of corruption eradication in legislation. Over time, the role of the KPK in eradicating corruption received intense attention from the public, both pro, and contra. The legislature wants to revitalize the implementation of the KPK's duties with several considerations, to prioritize prevention efforts through the revision of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission